2017
DOI: 10.1007/s11280-017-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging semantic resources in diversified query expansion

Abstract: A search query, being a very concise grounding of user intent, could potentially have many possible interpretations. Search engines hedge their bets by diversifying top results to cover multiple such possibilities so that the user is likely to be satisfied, whatever be her intended interpretation. Diversified Query Expansion is the problem of diversifying query expansion suggestions, so that the user can specialize the query to better suit her intent, even before perusing search results. In this paper, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Such corresponding entities are then added to the index structure assuming more relevant documents will be retrieved accordingly. Several studies have investigated and confirmed the impact of employing semantic resources on improving the quality of the indexing and retrieval process (Krishnan et al, 2018;Hyvönen and Rantala, 2019). However, we argue that existing semantic recourses still suffer from a number of limitations that hinder their actual exploitation in practical application domains.…”
Section: Introductionmentioning
confidence: 83%
“…Such corresponding entities are then added to the index structure assuming more relevant documents will be retrieved accordingly. Several studies have investigated and confirmed the impact of employing semantic resources on improving the quality of the indexing and retrieval process (Krishnan et al, 2018;Hyvönen and Rantala, 2019). However, we argue that existing semantic recourses still suffer from a number of limitations that hinder their actual exploitation in practical application domains.…”
Section: Introductionmentioning
confidence: 83%
“…We are considering ways in which this binary labelling can be relaxed in order to offer more fine-grained labellings, staying within the graph-based framework. Other directions include generating interpretable results [3] and enriching semantic query expansion (e.g., [19]) with veracity orientation.…”
Section: Discussionmentioning
confidence: 99%
“…After that, we decrease the corresponding edge common neighbor numbers that have been changed due to the removal of (u, v) for the edge incident to (u, v) (line 10-15) based on Definition 6.6. Similarly, for each negative edge not satisfying the conditions in Lemma 6.7, we remove it and decrease the corresponding edge common neighbor numbers (line [17][18][19][20][21][22][23][24]. The algorithm terminates when all the edges satisfy conditions in Lemma 6.7.…”
Section: Algorithm 5 Edgereductionmentioning
confidence: 99%
“…In such signed networks, our model can discover synonym groups that are antonymous with each other, such as, {interior, internal, intimate} and {away, foreign, outer, outside, remote}. These discovered groups may be further used in applications such as automatic question generation [24] and semantic expansion [22]. Contributions.…”
Section: Introductionmentioning
confidence: 99%